2015
DOI: 10.5194/bg-12-4607-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of soluble P fertilizers and insoluble rock phosphate in response to phosphate-solubilizing bacteria and poultry manure and their effect on the growth and P utilization efficiency of chilli (<i>Capsicum annuum</i> L.)

Abstract: Abstract. The ability of soil microorganisms and organic manure to convert insoluble phosphorus (P) to an accessible form offers a biological rescue system for improving P utilization efficiency in soil-plant systems. Our objective was to examine the P mineralization potential of two soluble P fertilizers (SPF), i.e., single superphosphate (SSP) and diammonium phosphate (DAP), and of insoluble rock phosphate (RP) with and without phosphate-solubilizing bacteria (PSB) and poultry manure (PM) and their subsequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 40 publications
9
40
0
Order By: Relevance
“…In a recent study, inoculation of rice with Burkholderia, Enterobacter, Paenibacillus , and Pseudomonas significantly increased the growth characteristics and nutrient contents in rice fertilized with Bayóvar RP compared to Bayóvar RP without inoculation ( da Costa et al, ). Similar stimulating effects of PSBs and organic amendments on plant biomass and P accumulation in different crops treated with RP had also been reported earlier by different workers ( Sharma et al, ; Panhwar et al, ; Saleem et al, ; Abbasi et al, ; Billah and Bano , ).The higher response of plant biomass and P accumulation in plants due to PSBs and PM was attributed to the solubilization and mobilization of native and applied P due to the acidic environment prevailing during the secretion of organic acids from PSBs and PM ( Chen et al, ; Nishanth and Biswas , ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In a recent study, inoculation of rice with Burkholderia, Enterobacter, Paenibacillus , and Pseudomonas significantly increased the growth characteristics and nutrient contents in rice fertilized with Bayóvar RP compared to Bayóvar RP without inoculation ( da Costa et al, ). Similar stimulating effects of PSBs and organic amendments on plant biomass and P accumulation in different crops treated with RP had also been reported earlier by different workers ( Sharma et al, ; Panhwar et al, ; Saleem et al, ; Abbasi et al, ; Billah and Bano , ).The higher response of plant biomass and P accumulation in plants due to PSBs and PM was attributed to the solubilization and mobilization of native and applied P due to the acidic environment prevailing during the secretion of organic acids from PSBs and PM ( Chen et al, ; Nishanth and Biswas , ).…”
Section: Discussionsupporting
confidence: 87%
“…The maximum relative increase in P released from RP+PM+PSBs over RP+PM was 52% recorded in RP+PM+PSB 3 treatment at 60 d incubation. Similar effects of bio‐ and organic amendments on P availability and P recovery from RP had also been reported earlier ( Aria et al, ; Alzoubi and Gaibore , ; Abbasi et al, ). The mechanisms involved in the potential of PSBs to solubilize P complexes or insoluble phosphates are well known and have been attributed to the processes of acidification, chelation, exchange reactions, and the production of organic acids as reported by Chen et al ().…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This phenomenon was found after one month and four months of incubation, indicated that the increasing of rock phosphate dosage followed by the increasing of potential P in the soil. Meanwhile, reversely biofertilizer decreased potential P. This finding was contradictory to [17] where application of rock phosphate and phosphate solubilizing bacteria increased the potential P. Figures 3 and 4 inform the correlation between Potential P and P-retention and between potential P and available P after one and four months of incubation. Figure 3 informs that potential P increased as the P retention decreased.…”
Section: Potential Pmentioning
confidence: 81%